Isolated epididymal injury after blunt scrotal trauma from high velocity paintball round - Dale, Robert; Hoag, Nathan A. (Canadian Urological Association Journal, 2015)
Isolated epididymal injury without associated underlying scrotal or testicular injury in the setting of blunt trauma is exceedingly rare. We present a case of an isolated epididymal injury incurred after scrotal trauma from a high velocity paintball round. Ultrasound demonstrated an enlarged, hypoechoic left epididymis with no evidence of underlying testicular injury. This case highlights the importance of obtaining imaging to evaluate for signs of testicular rupture, potentially obviating the need for surgery. It also reinforces the need for appropriate protective gear when participating in activities with potential for high velocity scrotal trauma.